Macroeconomics under the microscope: Heterogeneity and uncertainty - Emil Holst Partsch (University of Copenhagen, Department of Economics, 2022)
This Ph.D. thesis consists of four self-contained chapters, which all investigate macroeconomic questions from a micro perspective: through structural models with either full distributional heterogeneity or approximations thereof, and in one case, through microdata. In addition, all projects are bound together by incorporating risk and/or uncertainty as drivers of outcomes. [...]
Keywords: 330